Ownership Concentration and Transfer Pricing Decisions: Evidence from Indonesian Consumer Non-Cyclical Firms - Heliani Heliani; Dina Amalia (West Science Social and Humanities Studies, 2025)
Globalization has had a significant impact on the dynamics of the global economy, including the international business practices carried out by multinational companies. One of the consequences of this phenomenon is the increasing flow of transactions between related entities, known as Transfer Pricing. Transfer pricing refers to a company's policy in determining the transfer price of transactions involving goods, services, intangible assets, or financial transactions between affiliated companies. Multinational companies often utilize transfer pricing by manipulating transfer prices to reduce the amount of tax payable to the state in order to maximize profits. The purpose of this study is to examine the effect of Intangible Assets and Tunneling Incentive on the decision of companies to engage in Transfer Pricing. The observation period of this study covers the years 2020 to 2024. The research sample consists of consumer non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sampling method employed was purposive sampling, resulting in a total of 115 observations. Data were processed using E-Views with panel data regression analysis under the Random Effect Model (REM). Transfer Pricing was measured using the ratio of related-party receivables to total receivables, Intangible Assets were measured using the ratio of intangible assets to total assets, and Tunneling Incentive was measured using the ratio of the largest shareholding to total outstanding shares. The results indicate that Intangible Assets have no significant effect on the decision to engage in Transfer Pricing, whereas Tunneling Incentive has a significant effect, suggesting that the proportion of share ownership influences a company's tendency to conduct Transfer Pricing. Furthermore, the study finds no simultaneous effect of Intangible Assets and Tunneling Incentive on the decision to engage in Transfer Pricing.